2022
DOI: 10.1136/bmjopen-2021-050979
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of living with long COVID and of accessing healthcare services: a qualitative systematic review

Abstract: ObjectiveTo explore the experiences of people living with long COVID and how they perceive the healthcare services available to them.DesignQualitative systematic review.Data sourcesElectronic literature searches of websites, bibliographic databases and discussion forums, including PubMed LitCovid, Proquest COVID, EPPI Centre living systematic map of evidence, medRxiv, bioRxiv, Medline, Psychinfo and Web of Science Core Collection were conducted to identify qualitative literature published in English up to 13 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
129
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 26 publications
10
129
3
1
Order By: Relevance
“…The most often used definition is: symptoms persisting for more than three months from the onset of acute COVID-19 9,10 . Extended symptoms have been classified as probably infection-related (up to 4-5 weeks), acute post-COVID symptoms (weeks [5][6][7][8][9][10][11][12], prolonged post-COVID symptoms (weeks [12][13][14][15][16][17][18][19][20][21][22][23][24], and chronic post-COVID symptoms (more than 24 weeks) 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most often used definition is: symptoms persisting for more than three months from the onset of acute COVID-19 9,10 . Extended symptoms have been classified as probably infection-related (up to 4-5 weeks), acute post-COVID symptoms (weeks [5][6][7][8][9][10][11][12], prolonged post-COVID symptoms (weeks [12][13][14][15][16][17][18][19][20][21][22][23][24], and chronic post-COVID symptoms (more than 24 weeks) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Following the acute phase of COVID-19, the presence of more than one symptom is quite prevalent, occurring in 74% 11,12 to 87.4 percent of all infected patients 12 . Initially, patient concerns were dismissed as mental health problems, including worry or stress 13 , but later it became clear that people who suffer from longterm COVID have a wide range of physical and mental symptoms [14][15][16] . Among the various symptoms associated with Long COVID, the most frequently reported symptoms are fatigue and dyspnoea 9,11,17,18 , post-traumatic stress symptoms 19,20 , concentration and memory problems 21,22 , and anxiety and depression 4,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of long Covid, people with this condition have reported disbelief and undue psychologisation from healthcare professionals (Ladds et al 2020;Macpherson et al 2022;Kingstone et al 2020), although the referenced studies also demonstrate that not all (micro-level) healthcare encounters have been reported as negative. In fact, the barriers to understanding long Covid, and validation of patient narrative, appear predominantly structural; lack of adequate explanatory healthcare model, unpreparedness of health services to provide appropriate healthcare and a culture of privileging 'objective' markers and clinical expertise over patient narrative have all been discussed and challenged in this regard (see Maxwell and Poole 2021;Hunt 2020;Alwan et al 2020).…”
Section: Long Covid Through a Disability Studies Lensmentioning
confidence: 99%
“…It has also been argued that ableist discourse-for example the 'recover or die' narrative-further embedded in the biopolitical ideology of neoliberalism, permeates healthcare and the social security system and negatively impacts on chronically ill and disabled people, including people with long Covid (Hunt, Blease, and Geraghty 2022). Associated binaries discernible in COVID-19 discourse, including 'mild infection or death' (Kingstone et al 2020) and 'non-hospitalised (non-serious) or hospitalised (serious)' (Macpherson et al 2022), are likely associated with reported difficulties accessing social security benefits, workplace accommodations, sick certification, disability insurance and broader social support, alongside appropriate healthcare (see Ladds et al 2020;Davis et al 2021;Kingstone et al 2020). To determine whether such structural factors may be understood as facets of disability (oppression, disablism) as per the social relational model (Thomas 2007), a more detailed exploration of the experiences of people with long Covid is indicated.…”
Section: Long Covid Through a Disability Studies Lensmentioning
confidence: 99%
“…As part of this collaboration, a qualitative systematic review to understand the experience of long COVID from patients’ perspectives was recently published. 8…”
Section: The Need To Adapt and Collaboratementioning
confidence: 99%